Innovation in Teaching Writing Folktales, Its Organization and Sentence Structure - *, Siyaswatia; Kinasiha, Titah (Sebelas Maret University, 2016)
The main purpose of learning English is to be able to communicate with other people either orally or written. One of the communication forms is writing. The role of writing is very important in many aspects. Realizing how important writing is, this paper explains innovation in teaching writing folktales, its organization and sentence structure. The purpose of the study is to know the organization and sentence structure in teaching writing at the university students. Students mostly donât pay attention to the sentence structures used in writing. In this study, the writer wants to describe sentence structure to build up a good writing particularly in writing folktales. Some related theories used by the writer to analyse writing. In this study, the writer uses descriptive approach. All the words, phrases, and sentences are described by the writer based on their organization and sentence structure. The analysis of writing is done through collecting, classifying, reducing, selecting, displaying, and concluding some related theory on how to build up an excellent sentence structure. The writer hopes that this study will be able to help the students to make a good writing folktales easily.